Micro area based spatial distribution of apple scab in an organic apple orchard - Holb, I. J.; Lakatos, P.; Abonyi, F. (International Journal of Horticultural Science, 2015)
In this study, the objective was to report a two-year investigation on micro area based spatial distribution of apple scab in an organic apple orchard. Results showed that number of symptomatic plant part ranged between 587 and 623 on leaf and between 46 and 78 on fruit for an individual tree. Number of asymptomatic plant part ranged between 1034 and 1321 on leaf and between 119 and 193 on fruit. Disease incidence ranged between 35 and 40% on leaf and between 27 and 33% on fruit. Disease aggregation index ranged between 0.115 and 0.298 on leaf and between 0.117 and 0.221 on fruit. Three of the four trees showed significant within canopy aggregation of disease for leaf apple scab symptoms in both years. For fruit apple scab, two of the four trees showed significant random patterns in both years.